Seventeen Point Plan [Information document] - Christin Bolewski (2013)
‘Seventeen Point Plan’ is a digital video animation, experimental documentary or animated documentary, 3,00min. It investigates the potential of animated documentary to create a digital video scroll that consists solely of documentary photography, text documents and audio recordings related to the Chinese invasion of Tibet in 1951. After the Chinese invasion of Tibet the Tibetan government is forced to sign the Seventeen Point Agreement for the Peaceful Liberation of Tibet with the People’s Republic of China on March 23, 1951. The people of Tibet have not given up hope of somehow driving out their oppressors even after 63 years of occupation.